A rare case of reversible paraplegia due to extramedullary hematopoiesis in a patient with thalassemia intermedia - Aysha I.Z. Badawi; Mona I. Nabih; Noha K.H.M. Khalil; Mohamed A.A. ELnady; Sarra A. Hassan (SpringerOpen, 2014)
30 yrs old man is known to have thalassemia intermedia presented with bilateral lower limb weakness and sphincteric troubles with loss of deep sensations, the motor power of the muscles and precipitancy of urine improved after blood transfusion, laboratory investigations and MRI dorsolumbar spine confirm the diagnosis of extramedullary haematopoiesis.